Absorption characteristics of napa soil as congo red dye adsorbent in solution with continuous system - Illyas Md Isa (Tanjong Malim, 2021)
Absorption characteristics of napa soil as congo red dye adsorbent in solution with continuous system by Illyas Md Isa